Bureaucratic Morality in India - O.P. Dwivedi and R.B. Jain (International Political Science Review 1988; 9; 205, 1988)
Independent India inherited the best administrative machinery among all developing nations, along with a highly moral and dedicated public service. However, bureaucratic immorality soon engulfed the political and administrative apparatus of the country. This paper focuses on the insidious aspects of such a change in India's bureaucratic culture, analyses briefly the state of political corruption and the misuse of constitutional and legal mechanisms, and concludes with lamentation on the prevailing Politico-bureaucratic morality and its impact on the body politic of India.